Steel, Administered Prices and Inflation: Reply - Adelman, M. A. (Quarterly Journal of Economics, 1961)
Journal Article Steel, Administered Prices and Inflation: Reply Get access M. A. Adelman M. A. Adelman Massachusetts Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 75, Issue 3, August 1961, Page 500, https://doi.org/10.2307/1885138 Published: 01 August 1961